PENGARUH LATIHAN BERPASANGAN TERHADAP KEMAMPUAN TENDANGAN SABIT PADA PENCAK SILAT SMA NEGERI 15 LUWU - Ahmad Ahmad (JURNAL PENDIDIKAN GLASSER, 2021)
Based on the pre-test results of students’ sickle kick ability of pencak silat extracurriculer at Sma Negeri 15 Luwu is still relatively low, this study aims to determine the effect of the use of paired exercises in improving sickle kick capability. This study used OneGroup Pre-test - Post-test Design design with a sample number of 15 people. Data collection using a grid of performance measurement instruments skills, as well as dataanalyzed with the help of SPSS 25. Results research shows that paired exercises have an influence on sickle kick capability, this can be seen from the average post-test result of 80.2667 higher than the average pre-test result of 66.4667. And 16,307 t test and ttabel value of 2,145. As such Ha accepted and H0 rejected. This means there is a significant influence of paired exercises toward the students’ ability of sickle kickin the pencak silat extracurriculer at Sma Negeri 15 Luwu.